Epidemiology, management and patient needs in myasthenia gravis: an Italian multistakeholder consensus based on Delphi methodology - Renato Mantegazza; Giuseppe Limongelli; Carlotta Galeone; Francesco Habetswallner; Raffaele Iorio; Giuseppina Annicchiarico; Maria Bonaria Uccheddu; Paolo Mariani (BMJ Open)
Objectives To provide comprehensive information on the burden of myasthenia gravis (MG) in Italy, including the unmet needs of patients and several other aspects related to the disease, based on skilled viewpoints of MG experts.Design Iterative analysis conducted in accordance with the best practices of the Delphi method, including anonymity, controlled feedback, and statistical stability of consensus.Setting and participants 24 clinicians, 18 public health experts and 4 patient associations experts completed all the Delphi iterations between 18 April and 3 July 2023, for a total of 46 participants from several Italian Regions.Outcome measures Five areas of investigation related to MG were examined: epidemiology in Italy and characteristics of disease; diagnostic issues and Italian patient journey; unmet needs during the acute and chronic phases of MG; quality of life; public health management of MG. Consensus in the Delphi iterations was defined by both the percentage level of agreement between panellists or the median value of the responses.Results We reported a high level of agreement (ie, >66.7% of panellists) on the prevalence and incidence of disease in Italy and on several management issues. A strong impact of MG on the quality of life of patients also emerged. Cross-agreement was achieved among different subgroups of panellists (ie, clinicians, public health experts and patient associations representatives) for most items proposed.Conclusions This study provided guidance for educational and practical aspects of MG in Italy, highlighted disease severity and its role on patients’ quality of life. A few gaps related to the handling of MG in Italy also emerged.